Clinical outcome of endoscopic therapy in patients with symptomatic pancreas divisum: a Dutch cohort study - de Jong, David M.; Stassen, Pauline M.; Poley, Jan Werner; Fockens, Paul; Timmer, Robin; Voermans, Rogier P.; Verdonk, Robert C.; Bruno, Marco J.; de Jonge, Pieter J.F. (Endoscopy International Open, 2021)
Background and study aims Although the majority of patients with pancreas divisum (PDiv) are asymptomatic, a subgroup present with recurrent pancreatitis or pain for which endoscopic therapy may be indicated. The aim of this study was to evaluate success rates and long-term outcomes of endoscopic treatment in patients with symptomatic PDiv. Patients and methods A multicenter, retrospective cohort study was performed. Patients with symptomatic PDiv presenting with recurrent acute pancreatitis (RAP), chronic pancreatitis (CP), or chronic abdominal pancreatic-type pain (CAP) who underwent endoscopic retrograde cholangiopancreatography (ERCP) between January 2000 and December 2019 were included. The primary outcome was clinical success, defined as either no recurrent episode of acute pancreatitis (AP) for RAP patients, no flares for CP patients, or absence of abdominal pain for patients with CAP after technically successful ERCP.Results In 60 of 81 patients (74.1 %) a technically successful papilla minor intervention was performed. Adverse events were reported in 30 patients (37 %), with post-ERCP pancreatitis in 18 patients. The clinical success rate for patients with at least 3 months of follow-up was 42.6 %, with higher rates of success among patients presenting with RAP (44.4 %) as compared to those with CP (33.3 %) or CAP (33.3 %). Long-term sustained response was present in 40.9 % of patients with a technically successful intervention. In patients with RAP who did not completely respond to treatment, the mean number of AP episodes after treatment decreased significantly from 3.5 to 1.1 per year, and subsequently the interval between AP episodes increased from 278 to 690 days (P = 0.0006). A potential predictive factor of failure of clinical success after technically successful ERCP, at univariate analysis, was male sex (OR = 0.25, P = 0.02). Conclusions Endoscopic therapy in patients with symptomatic PDiv is moderately effective, with its highest yield in patients presenting with RAP. Future studies are needed to assess factors predictive for success of endoscopic therapy and potential risk factors for relapse after ERCP.